2007
DOI: 10.1056/nejmoa065368
|View full text |Cite|
|
Sign up to set email alerts
|

Live Attenuated versus Inactivated Influenza Vaccine in Infants and Young Children

Abstract: Among young children, live attenuated vaccine had significantly better efficacy than inactivated vaccine. An evaluation of the risks and benefits indicates that live attenuated vaccine should be a highly effective, safe vaccine for children 12 to 59 months of age who do not have a history of asthma or wheezing. (ClinicalTrials.gov number, NCT00128167 [ClinicalTrials.gov].).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
574
6
20

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 752 publications
(617 citation statements)
references
References 13 publications
17
574
6
20
Order By: Relevance
“…Seasonal influenza vaccination provided 20–77% in children depending on antigenic match, against laboratory‐confirmed influenza (Table 2). 18, 47, 48, 49, 50, 51, 52, 53, 54, 55 Vaccinating school children provided 23·3% (66·3–74·9) protection against influenza and indirect protection of 61% (5·8–84·7) for household contacts 56. Vaccinating pregnant women prevented laboratory‐confirmed influenza in both mothers (50%) and their infants up to 6 months of age (49–63%) 57, 58.…”
Section: Resultsmentioning
confidence: 99%
“…Seasonal influenza vaccination provided 20–77% in children depending on antigenic match, against laboratory‐confirmed influenza (Table 2). 18, 47, 48, 49, 50, 51, 52, 53, 54, 55 Vaccinating school children provided 23·3% (66·3–74·9) protection against influenza and indirect protection of 61% (5·8–84·7) for household contacts 56. Vaccinating pregnant women prevented laboratory‐confirmed influenza in both mothers (50%) and their infants up to 6 months of age (49–63%) 57, 58.…”
Section: Resultsmentioning
confidence: 99%
“…The efficacy of LAIV was analyzed for children 15–23 months, 24–35 months, 36–47 months, 48–59 months and ≥60 months of age. Study 2 was a multinational, double‐blind, head‐to‐head trial conducted during the 2004–2005 influenza season in children 6–59 months of age 3 . Efficacy of LAIV compared with TIV was analyzed for children 6–23 months, 24–35 months, 36–47 months and 48–59 months of age.…”
Section: Methodsmentioning
confidence: 99%
“…LAIV provided levels of efficacy against influenza illness that, in the three comparative studies conducted, were significantly higher than those provided by TIV 1 , 3 , 7 . In contrast, comparative studies in adults ≥18 years of age have demonstrated variable results; studies have demonstrated comparable protection of the two vaccines, 12 , 13 , 14 , 15 , 16 greater protection with TIV, 17 , 18 , 19 and, in some cases, greater protection with LAIV 19 .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, because of intranasal administration, LAIV has the potential to stimulate greater local anti-influenza immune responses than TIV (20)(21)(22). LAIV demonstrated greater reductions in influenza than TIV in HIV-uninfected children, against strains that were well-matched with strains in the vaccine, as well as against antigenically drifted strains not included in the vaccine administered (23)(24)(25)(26)(27)(28), and several studies have shown that the LAIV protective effect can extend beyond the year of administration (27,28).…”
Section: Introductionmentioning
confidence: 99%